2007
DOI: 10.1542/peds.2006-2023h
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonates: Mode of Action and Pharmacology

Abstract: The profound effects of the bisphosphonates on calcium metabolism were discovered over 30 years ago, and they are now well established as the major drugs used for the treatment of bone diseases associated with excessive resorption. Their principal uses are for Paget disease of bone, myeloma, bone metastases, and osteoporosis in adults, but there has been increasing and successful application in pediatric bone diseases, notably osteogenesis imperfecta. Bisphosphonates are structural analogues of inorganic pyrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
332
1
28

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(365 citation statements)
references
References 145 publications
4
332
1
28
Order By: Relevance
“…In the present study, we examined the commonly used biphosphonate molecule ZOL, because of its high biological activity in inducing inhibition of proliferation and apoptosis in several cancer cell lines [20]. We here reported that ZOL, the most potent nitrogen containing BP, causes The ability to form a colony from a single cell, may be seen as a surrogate of the invasive ability of the tumor cell [43].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the present study, we examined the commonly used biphosphonate molecule ZOL, because of its high biological activity in inducing inhibition of proliferation and apoptosis in several cancer cell lines [20]. We here reported that ZOL, the most potent nitrogen containing BP, causes The ability to form a colony from a single cell, may be seen as a surrogate of the invasive ability of the tumor cell [43].…”
Section: Discussionmentioning
confidence: 97%
“…The antiproliferative effect of pamidronate in human and rat osteosarcoma cells has recently been demonstrated in vitro [18,19]. BPs can be divided into two distinct pharmacological classes based on their molecular mechanisms of action [20]. Non-nitrogencontaining BPs, such as clodronate and etidronate, are metabolized intracellularly as cytotoxic analogues of ATP and thus inhibit osteoclast activity [21].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional management for patients with OI consisted of supplementation with vitamin D and minerals, or administration of bisphosphonates [8,[12][13][14][15]. However, these methods did not ameliorate the symptoms of OI [12].…”
Section: Introductionmentioning
confidence: 99%
“…BPs are widely used to inhibit osteoclastic activity in benign and malignant bone diseases, such as Paget's disease, osteoporosis or osteolytic tumor bone metastases [1][2][3]. The nitrogen containing-BPs (N-BPs) are more effective and are able to interfere with the metabolism of mevalonate, leading to inhibition of the prenylation of small GTP-binding proteins (Ras, Rho…) [4,5].…”
Section: Introductionmentioning
confidence: 99%